Welcome to Westonci.ca, the Q&A platform where your questions are met with detailed answers from experienced experts. Find reliable answers to your questions from a wide community of knowledgeable experts on our user-friendly Q&A platform. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
Answer:
c = -9
Step-by-step explanation:
4c + 11 = -25
4c = -25 - 11
4c = -36
c = -36 : 4
c = -9
or
4c + 11 + 25 = 0
4c + 36 = 0
c = (-36)/4
c = -9
-------------------
check
4 *(-9) + 11 = -25
-36 + 11 = -25
-25 = -25
the answer is good
Answer:
c= -9
Step-by-step explanation:
1. 4c + 11 = -25
2. Put all like terms together and change the sign. In this case, the +11 will go to the right with the -25 and it will become -11.
Therefore:
4c= -25 -11
4c= -36
3. Make c the subject. Since 4 is being multiplied by c, when it goes to the right, it will divide.
Therefore:
c= -36/4
c= -9
Thanks for using our platform. We're always here to provide accurate and up-to-date answers to all your queries. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Get the answers you need at Westonci.ca. Stay informed by returning for our latest expert advice.